2009
DOI: 10.1248/cpb.57.43
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Drying of Proteins in Glass Solids Formed by Basic Amino Acids and Dicarboxylic Acids

Abstract: 43Freeze-drying is a popular method of ensuring the stability of proteins that are not stable enough in aqueous solutions during the period required for storage and distribution. 1,2) Various freeze-dried protein formulations contain excipients (e.g., sugars, polymers, and amino acids) that protect proteins from physical and chemical changes. Disaccharides (e.g., sucrose, trehalose) are the most popular among them because they stabilize proteins both thermodynamically and kinetically in aqueous solutions and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 28 publications
5
45
0
Order By: Relevance
“…T g itself depends on the experimental procedure, 8,53 which can lead to strong deviations in T g between different studies. In our experiments, values of 214.3 K and 218.8 K were obtained for two different concentrations, exhibiting close agreement with the values given by Kadoya et al 72 and Izutsu et al 73 The T m -and T hom -curves in Fig. 1 (dashed and dashdotted lines) are fit functions of the form of a fourth degree polynomial, omitting the third degree.…”
Section: A Binary Solutionssupporting
confidence: 91%
See 2 more Smart Citations
“…T g itself depends on the experimental procedure, 8,53 which can lead to strong deviations in T g between different studies. In our experiments, values of 214.3 K and 218.8 K were obtained for two different concentrations, exhibiting close agreement with the values given by Kadoya et al 72 and Izutsu et al 73 The T m -and T hom -curves in Fig. 1 (dashed and dashdotted lines) are fit functions of the form of a fourth degree polynomial, omitting the third degree.…”
Section: A Binary Solutionssupporting
confidence: 91%
“…9 and 68). T m and T hom from Murray, 9 T m and T g from Maltini et al, 68 T g from Lu and Zografi, 69 ★ T g from Kadoya et al 72 and Izutsu et al 73 If not explicitly indicated in the plot, the errorbars are within the symbol size. TABLE II.…”
Section: A Binary Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was expected that the high transition temperatures (T g ′) of the L-arginine mixture frozen solutions would allow efficient primary drying at higher product temperatures. 5) However, the different molecular interactions contributing to glass formation of the disaccharide and the amino acid-carboxylic acid mixture systems require the assessment of the relationship between the thermal transition and collapse phenomena for formulation and process development. Crystallization of L-arginine in frozen aqueous solutions was also studied.…”
mentioning
confidence: 99%
“…32,33) Our previous study also showed contribution of rigid molecular interactions to form glass-state solids by co-lyophilization of citric acid an L-arginine. 34) Many protein solutions have their T g Ј at temperatures (approx. Ϫ10°C) higher than those of smaller molecules.…”
Section: Discussionmentioning
confidence: 99%